HEALTHY LIVING PATTERNS TO PREVENT COVID-19 - Indri Seta Septadina (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Viruses are one of the causes of infectious diseases that need to be watched out for. In the last 20 years, several viral diseases have caused epidemics such as severe acute respiratory syndrome coronavirus (SARS-CoV) in 2002-2003, influenza H1N1 in 2009 and Middle East Respiratory syndrome (MERS-CoV) which was first identified in Saudi Arabia in year 2012. On December 31, 2019, China reported a case of mysterious pneumonia of unknown cause. Within 3 days, the number of patients with these cases was 44 patients and continues to increase until now there are millions of cases. Initially, the epidemiological data showed that 66% of patients were related to or exposed to a seafood market or live market in Wuhan, Hubei Province, China. Samples of isolates from patients were studied with the results showing the presence of coronavirus infection, a new type of betacoronavirus, named 2019 novel Coronavirus (2019-nCoV). On February 11, 2020, the World Health Organization named the new virus SARS-CoV-2 and the disease name as Coronavirus Disease 2019 (COVID-19). The corona virus is the main pathogen causing an outbreak of respiratory disease. On March 11, 2020, WHO announced that COVID-19 was becoming a pandemic in the world.